Solvent effects on the spectral diffusion dynamics of chlorophylls - Sim, Jamie Hung Ni (Nanyang Technological University, 2020)
Chlorophyll a (Chl a) and Chlorophyll b (Chl a) are pigment molecules that are vital to the process of photosynthesis in green plants. These molecules bind to the protein matrix through ligation with side groups in the protein scaffold. The manner in which protein side groups bind to the Mg2+ ions play an important role in the function of Chls, tuning the energy based on the nature of Chl-ligand interactions which aids in the acceptance of light energy for photosynthesis. In this thesis, we aim to understand the relaxation dynamics of Chl a and Chl b monomers in solvents to provide a greater insight of its behaviour in the protein matrix. We use ultrafast two-dimensional electronic spectroscopy (2DES) to determine the frequency fluctuation correlation function (FFCF) in a range of solvents, measuring the spectral diffusion process of the Qy transition using the Centre Line Slope (CLS) method. In this thesis, we experiment with how the interactions between the surrounding solvent molecules and Chl affect the FFCF in Chl a and Chl b. In chapter 2, the factor discussed is the polarity and hydrogen bonding ability of the surrounding solvent. We measure the FFCF decay for Chl a and Chl b in a protic solvent, methanol and aprotic solvents, tetrahydrofuran and diethyl ether, all of which have varying polarity. We find that the polarity of the solvent does not affect the FFCF decay but a significant ~ 40 ps component is only present in the protic solvent, methanol. We also observe that Chl b exhibits a higher level of inhomogeneous broadening as compared to Chl a despite their similarities in molecular structure. Next, in chapter 3 we discuss the effect of Lewis basicity of the surrounding solvent. We perform 2DES experiments on Chls in solvents of various Lewis basicity, which is measured by the pKa and BF3 affinity. From the decay of the FFCF, we find that certain timescales of the spectral diffusion dynamics are correlated to the Lewis basicity of the solvent. Additionally, control experiments and theoretical calculations are used to try and better understand the molecular mechanism causing this correlation. The sensitivity of Chls to the Lewis basicity of their surrounding solvent is due to the dynamics of the dative bond between the Mg2+ of the Chl and the heteroatom of the solvent molecule. We are able to show that the 2DES method can act as a sensitive probe to study the molecular mechanism associated with the Lewis basicity of a solvent.